Experimental model of human corpus cavernosum smooth muscle relaxation - Rommel P. Regadas; Maria E. A. Moraes; Francisco J. C. Mesquita; Joao B. G. Cerqueira; Lucio F. Gonzaga-Silva (International Brazilian Journal of Urology, 2010)
PURPOSE: To describe a technique for en bloc harvesting of the corpus cavernosum, cavernous artery and urethra from transplant organ donors and contraction-relaxation experiments with corpus cavernosum smooth muscle. MATERIALS AND METHODS: The corpus cavernosum was dissected to the point of attachment with the crus penis. A 3 cm segment (corpus cavernosum and urethra) was isolated and placed in ice-cold sterile transportation buffer. Under magnification, the cavernous artery was dissected. Thus, 2 cm fragments of cavernous artery and corpus cavernosum were obtained. Strips measuring 3 x 3 x 8 mm3 were then mounted vertically in an isolated organ bath device. Contractions were measured isometrically with a Narco-Biosystems force displacement transducer (model F-60, Narco-Biosystems, Houston, TX, USA) and recorded on a 4-channel Narco-Biosystems desk model polygraph. RESULTS: Phenylephrine (1µM) was used to induce tonic contractions in the corpus cavernosum (3 - 5 g tension) and cavernous artery (0.5 - 1g tension) until reaching a plateau. After precontraction, smooth muscle relaxants were used to produce relaxation-response curves (10-12M to 10-4 M). Sodium nitroprusside was used as a relaxation control. CONCLUSION: The harvesting technique and the smooth muscle contraction-relaxation model described in this study were shown to be useful instruments in the search for new drugs for the treatment of human erectile dysfunction.